Poverty as a Driver of Stigma among Finnish Children during the Covid‑19 Pandemic– Evidence from the 2021 Children’s Voice Survey - Vuorenlinna Emily; Välimäki Sanni; Lindberg Marja; Sarkia Aino; Hakovirta Mia; Nygård Mikael (SPRINGER, 2025)
Stigma is a social problem that can have severe outcomes on both individuals and society. Previous research shows that children's experiences of stigma may increase during times of stress and hardship such as the Covid-19 pandemic, but also that poverty and a lack of resources can create stigmatization. However, both stigma and poverty are multidimensional phenomena that have been investigated mainly among adults using single indicators. This article contributes to literature by studying children's experiences of stigma and its relation to poverty by using a multidimensional approach. More specifically, it investigates Finnish children's experienced and internalized stigma during the second year of the Covid-19 pandemic, and analyses how these dimensions are associated with subjective poverty and material deprivation. We use data from the 2021 Children's Voice survey conducted by Save the Children, Finland. The results show that both dimensions of stigma are correlated with subjective poverty as well as material deprivation, even when controlling for socio-economic and other variables. Also low psychological wellbeing is a significant driver of both forms of stigma, while living in a one-parent household was significantly associated with internalized stigma, but not experienced stigma. By contrast, while higher self-esteem seem to reduce both forms of stigma, a higher number of good friends was found to only reduce experienced stigma. As there are both short- and long-term negative outcomes of stigma, for example in terms of mental health problems and social exclusion, child poverty should be taken seriously - especially during times of crises such as pandemics.